A bag contains 9 marbles: 2 are green, 3 are red, and 4 are blue. Melissa chooses a marble at random, and without putting it back, chooses another one at random. What is the probability that the first marble is red and the second is blue? Write your answer as a fraction in simplest form.

Answers

Answer 1

Answer: 1/6

Step-by-step explanation: There are 9 marbles in total. There are 3 red marbles out of 9, and the fraction is 3/9, simplified to 1/3. Since the marble is not being replaced, there are now 8 marbles. 4 of the 8 marbles are blue. The fraction is 4/8, simplified to 1/2. Multiply the fractions.

1/3 x 1/2 = 1/6

There’s a 1/6 chance.


Related Questions

Which is the graph of linear inequality 2 y > x – 2?

Answers

Answer:

Third graph

Step-by-step explanation:

We are determine whether which of the given graphs is that of the linear inequality [tex]2y>x-2[/tex].

We know that, on the graph the greater than sign ([tex]>[/tex]) represents the shaded part above the line and less than sign ([tex]<[/tex]) represents the shaded region below the line.

While the signs [tex]\leq[/tex] or [tex]\geq[/tex] is denoted by a solid line on the graph.

Therefore, the third graph represents the given inequality.

Answer:

The graph in the attached figure

Step-by-step explanation:

we have

2y > x-2

The solution of this inequality is the shaded area above the dotted line 2y=x-2

The graph in the attached figure

Which are correct representations of the inequality –3(2x – 5) < 5(2 – x)? Check all that apply.

x < 5
–6x – 5 < 10 – x
–6x + 15 < 10 – 5x



Answers

Answer:

[tex]-6x+15< 10-5x[/tex]

Step-by-step explanation:

we have

[tex]-3(2x-5) < 5(2-x)[/tex]

solve for x

eliminate the parenthesis (apply the distributive property)

[tex]-3*2x+3*5 < 5*2-5*x[/tex]

[tex]-6x+15< 10-5x[/tex] ---> correct representation of the inequality

Adds (5x-15) both sides

[tex]-6x+15+5x-15< 10-5x+5x-15[/tex]

[tex]-x< -5[/tex]

Multiply by -1 both sides

[tex]x>5[/tex]

the equation of a line in the point slope form is show below.​

Answers

Answer:

A 3

Step-by-step explanation:

y-9 = 3(x-9)

This is in point slope form

y-y1 = m(x-x1)

where (x1,y1) is the point and m is the slope

A point on the line is (9,9) and the slope is 3

Students observing a caterpillar crawl on a tree noticed that the caterpillar crawled upwards 38 of an inch every minute. The caterpillar was already 4.5 feet off the ground when the students began observing.

Which function represents the total number of inches the caterpillar crawls after x minutes?

f(x) = 4.5x + 3/8

f(x) = 54x + 3/8

f(x( = 3/8x + 54

f(x) = 3/8x + 4.5

Answers

Answer:

f(x) = 4.5x + 3/8

Answer: Third Option

[tex]f(x) = \frac{3}{8}x + 54[/tex]

Step-by-step explanation:

We want to propose an equation that models the distance traveled by the caterpillar as a function of time, we have a constant initial quantity of 4.5 feet and then we know that every minute the caterpillar advances 3/8 of an inch

Then the distance that the caterpillar to advanced after x minutes is:

[tex]f(x) = \frac{3}{8}x[/tex]

Then we know that initially the caterpillar was at a distance of 4.5 feet or 54 inch

Then the equation for the distance in inch is:

[tex]f(x) = \frac{3}{8}x + 54[/tex]

For Sophia's graduation party, several tables of the same width will be arranged end to end to form a serving table with a
total area of 75 ft. The total length of the tables will be two more than three times the width. Find the length and width of
the serving table so that Sophia can purchase the correct table cloth. Round your answers to the nearest tenth.
Area: 75 ft
Bw + 2​

Answers

Answer:

Width=4.7 ft

Length=16.1 ft

Step-by-step explanation:

Let the width of the table to be x ft

Then the length should be two more than three times the width= 2+3x ft

The area of the serving table should be 75 ft²

But you know the area of this table is calculated by multiplying the length by the width of the table

Hence, Area= length× width

Length=x ft  and width =2+3x ft

75ft²= (x ft) × (2+3x ft)

[tex]75=x*(2+3x)\\\\75=2x+3x^2\\\\3x^2+2x-75=0[/tex]

Apply the quadratic formula to solve this quadratic equation

The formula is ;

x= (-b ±√b²-4ac)÷2ac

where a=3, b=2 and c=-75

x= (-2 ± √2²-4×3×-75)÷(2×3)

x=(-2±√4+900)÷6

x=(-2±√904)÷6

x=(-2±30.1)÷6

x=(-2+30.1)÷6=4.683⇒4.7(nearest tenth)

or

x=(-2-30.1)÷6= -32.1÷6=-5.35⇒ -5.4

Taking the positive value

x=width =4.7 ft

2+3x= length= 2+3(4.7)=16.1 ft

Find the num
The sum of a number and its reciprocal 10/3. find the number 5​

Answers

Answer:

x=3 or x= 1/3

Step-by-step explanation:

Let the number = x

The reciprocal of the number = 1/x

According to the given statement:

x+1/x=10/3

x²+1/x=10/3

3(x²+1)=10x

3x²+3=10x

Move 10x to the L.H.S

3x²-10x+3=0

Break the middle term:

3x²-9x-x+3=0

3x(x-3)-1(x-3)=0

(x-3)(3x-1)=0

x-3=0 , 3x-1=0

x=0+3 ,  3x=0+1

x=3    , 3x=1

x=3    ,x = 1/3

So x=3 or x= 1/3 ....

The table shows the number of degrees the temperature increased or decreased over four days. On which day did the temperature change have the greatest magnitude?

Answers

The correct answer is Friday

Find the mean of the data set that consists of 3, 11, 4, 3, 10, 6, 4, 5.
A. 3 and 4
B. 4.5
C. 5.75
D. 5.25

Answers

Answer:

5.75

Step-by-step explanation:

[tex]3 + 11 + 4 + 3 + 10 + 6 + 4 + 5 = 46 \\ 46 \div 8 = 5.75[/tex]

The total amount of numbers are : 8

To find the mean, we calculate the sum of all values and divide that sum by the amount of numbers there are.

PLEASE DO MARK ME AS BRAINLIEST IF MY ANSWER IS HELPFUL :)

If triangle DEC congruent to triangle BEC, which is true by CPCTC?

Answers

Answer:

The correct answer is the second one

Step-by-step explanation:

Line BE and ED are congruent because they are the same length and E is the mid line.

Answer:

second option is correct

Step-by-step explanation:

By the given

ΔDEC≅ΔBEC

which means triangle DEC is congruent to triangle BEC

then by CPCTC (corresponding parts of congruent triangle are congruent)

there every side and angle of DEC will be equal to BEC

⇒BE= DE (by CPCTC)

hence second option is correct

Write the expression in complete factored form. 2n^2(q+8)-(q+8)=

Answers

(q+8)(2n^2-1)

I think this is the correct form.

Express each ratio as a fraction in lowest terms.
1) 77 to 490
2) 35 to 135
3) 65:1001 ​

Answers

1. 11/70
2. 7/27
3. 5/77
You just have to divide both the numerator and denominator by a common factor

Add the two expressions.

−2.4n−3 and −7.8n+2

Enter your answer in the box.

Answers

Answer:

-10.2n - 1

Step-by-step explanation:

−2.4n − 3 + (−7.8n + 2) =

= -2.4n - 7.8n - 3 + 2

= -10.2n - 1

Answer:

-10.2n -1

Step-by-step explanation:

−2.4n−3 + −7.8n+2

Combine like terms

−2.4n −7.8n -3+2

-10.2n -1

Which is the best estimate of the circumference of this circle?

Answers

Answer:

12 is the best estimate

Answer:

option A.

Step-by-step explanation:

We have to find the circumference of the given circle with radius 2 units.

Since formula to calculate circumference of a circle is = 2πr

Where r = radius of the circle.

Circumference = 2 × (3.14) × (2)

                        =  4 × 3.14

                        = 12.56

So approximate value will be option A.

A triangle has two sides of lengths 10 and 14. What value could the third side be?

Answers

Answer:B, C, D, E.

Step-by-step explanation:

The third side of a triangle with two sides measuring 10 and 14 units must be greater than 4 and less than 24 units. This is determined using the Triangle Inequality Theorem.

The possible values for the third side of a triangle with sides of lengths 10 and 14 can be found using the Triangle Inequality Theorem.

Add the two given side lengths: 10 + 14 = 24.

To find the range of possible values for the third side, subtract the two given side lengths from the total: 24 - 10 = 14, and 24 - 14 = 10.

Therefore, the third side of the triangle must have a length greater than 4 but less than 24.

A: What are the solutions to the quadratic equation?

B: which statements accurately interpret the solution?

Answers

Answer:

A. x = -1 or x = 3B. first

Step-by-step explanation:

[tex]x^2-2x-3=0\\\\x^2+x-3x-3=0\\\\x(x+1)-3(x+1)=0\\\\(x+1)(x-3)=0\iff x+1=0\ \vee\ x-3=0\\\\x+1=0\qquad\text{subtract 1 from both sides}\\x=-1\\\\x-3=0\qquad\text{add 3 to both sides}\\x=3[/tex]

The fuel consumption in miles per gallon for a car varies inversely with its weight. Suppose a car that weighs 2800 pounds get 33 miles per gallon on the highway. Write the equation that relates y, the fuel consumption in miles per gallon, to the car's weight, w pounds.​

Answers

Answer:

y=0.01179/w

Step-by-step explanation:

First understand that the fuel consumption in miles per gallon is inversely proportional to the weight of a car.

If y is the fuel consumption in miles per gallon and w is weight of car in pounds . you can write the first statement as;

y∝1/w

Introduce a constant value for proportionality, k

y=k/w....................make k subject of the formula by multiplying both sides by 1/w

k=y/w

Given in the question that ;

w=2800

y=33

k=?

To find k , apply the formula that you derived above

k=y/w

k=33/2800 =0.011785⇒0.01178(4 significant figures)

Rewrite the formula as

y=k/w  ⇒ y=0.01179/w

The equation that relates y and w is;

y=0.01179/w

Final answer:

The fuel consumption in miles per gallon for a car varies inversely with its weight and can be represented mathematically by the inverse proportionality relationship y = k/w. Substituting the given values gives us the constant k = 92400, so the final equation is y = 92400/w.

Explanation:

This problem can be defined mathematically by an inverse proportionality relationship, expressed as y = k/w, where k is a constant, y is the fuel consumption in miles per gallon, and w is the weight of the car in pounds.

To find the value of k, we can substitute the given values into the equation. This gives us 33 = k/2800, which simplifies to k = 33 * 2800, or k = 92400.

So, the equation that relates the mileage per gallon, y, to the weight of the car, w, is y = 92400/w. This means the fuel efficiency of a car decreases as its weight increases, thus heavier cars tend to have lower miles per gallon.

Learn more about Inverse Proportionality here:

https://brainly.com/question/14437120

#SPJ3

A 26 foot rope is used to brace a tent pole at the county fair. the rope is anchored 10 feet from the box of the pole. How tall is the pole? (answers above^^)

Answers

Using the Pythagorean theorem a^2 + b^2 = c^2 where a and b are the side and bottom of the triangle and c is the hypotenuse ( length of rope).

Let the tent pole = a

Lhe distance from the pole be b = 10 ft.

The length of rope would vce c = 26 ft.

Now you have:

a^2 + 10^2 = 26^2

Simplify:

a^2 + 100 = 676

Now subtract 100 from each side:

a^2 = 576

To get a, take the square root of both sides:

a = √576

a = 24

The tent pole is B. 24 ft

The area of the triangle is given by the functions area of triangle A:x2 + x area of triangle B: x2 - 3x which functions represents the sum of the areas of the two triangles? 1. 4x 2.-4x 3.x2-4x 4.2x2-2x

Answers

Answer:

4.   2x^2 - 2x.

Step-by-step explanation:

Adding the 2 functions:

Area of the 2 triangles = x^2 + x + x^2 - 3x

= .2x^2 - 2x

Answer:

OPTION 4

Step-by-step explanation:

Let be f(x) the function that represents the area of Triangle A:

[tex]f(x)=x^2 + x[/tex]

Let be g(x) the function that represents the area of Triangle B:

[tex]g(x)=x^2 - 3x[/tex]

Then, you need to add the area of Triangle A and the area of Triangle B in order to find the sum of the areas (Let be h(x) the function that represents the sum of the the areas of triangles A and B):

Therefore, this is:

[tex]h(x)=(x^2 + x)+(x^2 - 3x)=x^2 + x+x^2 - 3x=2x^2-2x[/tex]

You can notice that this matches with the option 4.

A basket contains six apples and four peaches. You randomly select one piece of fruit and eat it. Then you randomly select another piece of fruit. The first piece of fruit is an apple and the second piece is a peach. Find the probability of this occuring.

Answers

Answer as a fraction: 4/15

Answer as a decimal: 0.267

The decimal version is approximate rounded to three decimal places.

=============================================================

Explanation:

6 apples, 4 peaches

6+4 = 10 pieces of fruit total

The probability of picking an apple is 6/10 = 3/5

After you pick and eat the apple, there are 10-1 = 9 pieces of fruit left. Also, the probability of picking a peach is 4/9, as there are 4 peaches out of 9 fruit left over.

Multiply out 3/5 and 4/9 to get (3/5)*(4/9) = (3*4)/(5*9) = 12/45 = 4/15

Using a calculator, 4/15 = 0.267 approximately.

Answer:

Fraction: [tex]\frac{4}{15}[/tex]

Decimal: [tex]0.2667[/tex]

Percent: 26.67%

Step-by-step explanation:

If the basket contains six apples and four peaches then the Total amount of fruit in the basket is (6+4) 10 pieces of fruit.

You reach in and randomly pick out an apple. Since there are only 4 apples, the probability of this happening was [tex]\frac{4}{10}[/tex] , and now there are only 9 pieces of fruit in the basket.

Now you reach in and randomly pick out a peach. Since there are 6 peaches, the probability of this happening is [tex]\frac{6}{9}[/tex]. Now we can find the probability of both of these things happening one after another by multiplying both probabilities together

[tex]\frac{4}{10} * \frac{6}{9}  = \frac{24}{90}[/tex]

[tex]\frac{24}{90} = \frac{4}{15}[/tex] ...... simplified

So we can see that the probability of you picking out an apple and a peach in sequence is [tex]\frac{4}{15}[/tex] or [tex]0.2667[/tex]

I hope this answered your question. If you have any more questions feel free to ask away at Brainly.

What is the solution to the equation below?
log 20х3 - 2logx = 4
x=25
x=50
x=250
x=500​

Answers

Answer:

x = 500.

Step-by-step explanation:

log20x^3 - 2logx = 4

By the laws of logs:

log20x^3 - logx^2 = 4

log(20x^3 / x^2) = 4

20x^3 / x^2 = 10^4

20x = 10,000

x = 10,000 / 20

x = 500.

The solution of the given logarithmic equation is x = 500.

What is a logarithmic equation?

Any equation in the variable x that contains a logarithm is called a logarithmic equation.

Given logarithmic equation

[tex]log20x^{3} -2logx=4[/tex]

Using [tex]mloga=loga^{m}[/tex]

[tex]log20x^{3} -logx^{2}=4[/tex]

Using [tex]loga-logb=log(\frac{a}{b})[/tex]

[tex]\frac{log20x^{3} }{x^{2} }=4[/tex]

[tex]log20x=4[/tex]

[tex]20x=10^{4}[/tex]

[tex]x=\frac{10000}{20}[/tex]

[tex]x=500[/tex]

The solution of the given logarithmic equation is x = 500.

Find out more information about logarithmic equation here

https://brainly.com/question/14411365

#SPJ2

[tex]4c - d - c - 3d[/tex]

Answers

[tex]\tt 4c-d-c-3d=3c-4d[/tex]

Answer:

3c -4d

Step-by-step explanation:

4c -d -c -3d

Combine like terms

4c -c     -d -3d

3c -4d

Consider the polynomial p(x)=x^3-9x^2+18x-25, which can be rewritten as p(x)=(x-7)(x^2-2x+4)+3. The number blank is the remainder when p(x) is divided by x-7, and so x-7 blank a factor of p(x). Fill in the two blanks with is, 3, 7,is not, or 0!!!!
PLEASE HELP. WILL MARK BRAINLIEST!!

Answers

Answer:

[tex]\boxed{\text{3; is not}}[/tex]

Step-by-step explanation:

[tex]\begin{array}{rcl}p(x) & = & (x - 7)(x^{2} - 2x + 4) + 3\\\\\dfrac{p(x)}{x - 7} & = &x^{2} - 2x + 4 + \dfrac{3 }{x-7 }\\\\\end{array}\\\\\text{The number }\boxed{\mathbf{3}}\text{ is the remainder when $p(x)$ is divided by $(x - 7)$,}\\\\\text{so $(x - 7)$ }\boxed{\textbf{is not}} \text{ a factor of $p(x)$.}[/tex]

Question number 8 please please fast

Answers

Answer:

[tex]a_n=-\frac{1}{n}[/tex]

[tex]a_6=-\frac{1}{6}[/tex] is our sixth term.

[tex]a_7=-\frac{1}{7}[/tex]  is our seventh term.

[tex]a_8=-\frac{1}{8}[/tex] is our eighth term.

Step-by-step explanation:

So every number in this sequence is -.

If you write 1 as 1/1, then you should see the numerator is constant one while the denominator is going up by 1 each time.

So the patter is

[tex]a_n=-\frac{1}{n}[/tex]

Test if you like:

n=1 gives us [tex]a_1=-\frac{1}{1}=-1[/tex] which is our first term.

n=2 gives us [tex]a_2=-\frac{1}{2}[/tex] which is our second term.

n=3 gives us [tex]a_3=-\frac{1}{3}[/tex] which is our third term.

n=4 gives us [tex]a_4=-\frac{1}{4}[/tex] which is our fourth term.

n=5 gives us [tex]a_5=-\frac{1}{5}[/tex] which is our fifth term.

Now we are going to use [tex]a_n=-\frac{1}{n}[/tex]

to write our next three terms:

n=6 gives us [tex]a_6=-\frac{1}{6}[/tex] which is our sixth term.

n=7 gives us [tex]a_7=-\frac{1}{7}[/tex] which is our seventh term.

n=8 gives us [tex]a_8=-\frac{1}{8}[/tex] which is our eighth term.

If f(x) = x^2 + 1 and g(x) = x - 4, which value is equivalent to (fºg)(10)?

Answers

Answer:

37

Step-by-step explanation:

Substitute x = 10 into g(x), then substitute the result into f(x)

g(10) = 10 - 4 = 6, then

f(6) = 6² + 1 = 36 + 1 = 37

Solve x - (-9) = -14. -23 23 -5 5

Answers

Answer:

-23 = x

Step-by-step explanation:

-(-9) = 9

The thing with double negatives is that they form a plus sign, so that is really a POSITIVE nine. Therefore you do the inverse to find x: -14 - 9 = -23.

I am joyous to assist you anytime.

Answer:

[tex]\Huge \boxed{X=-23}[/tex]

Step-by-step explanation:

[tex]\displaystyle x+9=-14[/tex]

[tex]\Large\textnormal{First, subtract by 9 from both sides of equation.}[/tex]

[tex]\displaystyle x+9-9=-14-9[/tex]

[tex]\Large\textnormal{Simplify, to find the answer.}[/tex]

[tex]\displaystyle -14-9=-23[/tex]

[tex]\Large\textnormal{x=-23, which is our answer.}[/tex]

how much must you deposit in an account that pays 6.25% interest compounded annually to have a balance of $700 after 2 years​

Answers

Answer:

[tex]\$620.07[/tex]  

Step-by-step explanation:

we know that    

The compound interest formula is equal to  

[tex]A=P(1+\frac{r}{n})^{nt}[/tex]  

where  

A is the Final Investment Value  

P is the Principal amount of money to be invested  

r is the rate of interest  in decimal

t is Number of Time Periods  

n is the number of times interest is compounded per year

in this problem we have  

[tex]t=2\ years\\A=\$700\\ r=0.0625\\n=1[/tex]  

substitute in the formula above  and solve for P

[tex]700=P*(1+\frac{0.0625}{1})^{2}[/tex]  

[tex]700=P*(1.0625)^{2}[/tex]  

[tex]P=700/(1.0625)^{2}[/tex]  

[tex]P=\$620.07[/tex]  

6 plus 9 rquals to 10 plus WHAT NUMBER????

Answers

Answer: 5.

Step-by-step explanation:

6+9 = 15

10 + x = 15

-10 -10

x = 5

Answer:

x=5

Step-by-step explanation:

6+9=10+x

15=10+x

x=15-10

x=5

Find an equation for the inverse of the function. f(x)=2x-3x/4

Answers

Answer:

f⁻¹(x) = (4x)/5

Step-by-step explanation:

f(x) = 2x - 3x/4.

Assume y=f(x). Therefore:

y = 2x - 3x/4.

Make x the subject in the above equation.

y = (2x(4) - 3x)/4.

y = 5x/4.

4y = 5x.

(4y)/5 = x.

x = (4y)/5.

Therefore:

f(y) = (4y)/5.

Replace y with x.

f⁻¹(x) = (4x)/5.

Therefore, the inverse of f(x) = 2x - 3x/4 is f⁻¹(x) = (4x)/5!!!

simplify. rewrite the expression in the form 9^n:

9^-3/9^12

Answers

Answer:

9 ^ (-15)

Step-by-step explanation:

9^-3/9^12

We know that a^b/ a^c = a^(b-c)

9^-3/9^12 = 9 ^(-3-12)

                  =9^(-15)

The expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form  [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]

From the question,

we are to rewrite the given expression (9^-3/9^12) in the form 9^n

First, write the expressions properly.

The given expression is

[tex]\frac{9^{-3}}{9^{12} }[/tex]

To rewrite the given expression in the form [tex]9^{n}[/tex], we will use the division law of indices

From the division law of indices, we have that

[tex]x^{y} \div x^{z}= x^{y-z}[/tex]

Then, the given expression becomes

[tex]\frac{9^{-3}}{9^{12} } = 9^{-3} \div 9^{12}[/tex]

[tex]= 9^{-3-12}[/tex]

[tex]=9^{-15}[/tex]

Hence, the expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form  [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]

Learn more here: https://brainly.com/question/18205419

Help please the graphs below Have the same shape. What is the equation of the blue graph

Answers

Answer:

D. G(x) = (x+2)^2

Step-by-step explanation:

We can easily solve this problem by graphing each case with a graphing calculator or any plotting tool.

The equations are

A. G(x) = (x-2)^2

B. G(x) = (x)^2 + 2

C. G(x) = (x)^2 -2

D. G(x) = (x+2)^2

Se attached image.

The correct option is

D. G(x) = (x+2)^2

Answer:

C. G(x)=x²-2

Step-by-step explanation:

The midpoint of the graph has been displaced from x=0 to x=-2. this is a negative displacement.

Therefore the new equation G(x)=x²-2

This is because there is no tilt in the graph so it is a replica of the red graph.

Other Questions
Is the following statement true or false?Each paragraph should focus on two or more ideas.truefalse Which of the following statements must be true if the net force on an object is zero? Choose all that apply.a)The object must have constant velocity.b)The object must be at rest.c)The object must be at the origin.d)The object must have zero acceleration. You have $60. The jacket you want costs $25.50 and 7% tax. what is the top tag price (excludes sales tax) left to also buy a pair of shorts? Other symptoms of fat embolism include all the following:a. AMSb. Drowsinessc. Seizuresd. petechiaee. Nodular rash Jamin wants to paint a wall in his bedroom. Not only does he need to buy paint, but he also needs to buy tape to tape off all sides of the wall and the window. How many feet of painter's tape will Jamin need to buy (assume no overlap)? [Note: The wall and window are both rectangular.]17.5 ft35 ft28 ft21 ft The main benefit of shielded twisted pair cabling over unshielded twisted pair is that STP is much more durable.a) True b) False Using the given points and line, determine the slope of the line. (1, 2) and (2, 1) Find an equation of the plane. The plane that passes through the line of intersection of the planes x z = 3 and y + 4z = 1 and is perpendicular to the plane x + y 4z = 4 What is the best coefficient of performance for a refrigerator that cools an environment at -26.0C and has heat transfer to another environment at 50.0C? Beginning a non-fiction essay with a storyA)brings fantasy to life B)honors the main character C)increases interestD)limits scope - The whole batch cost $28,000 and contained 140 items. Write the two rates (ratios) impliedby this statement. What would be the price for 200 items?Please show work B= [2 8] A= [3 0] 6 3 2 -1What is the BA What is the solution to the system?X+y+z=22x+y-z=-1 X=5-2z Which of the following is an integer?04 -12.50 0.454545... A bicycle with 0.80-m-diameter tires is coasting on a level road at 5.6 m/s . A small blue dot has been painted on the tread of the rear tire. Part A What is the angular speed of the tires? Express your answer in radians per second. = 14 rad/s Previous Answers Correct Part B What is the speed of the blue dot when it is 0.80 m above the road? If f(x) = -x + 8 and g(x) = x^4, what is (gf)(2)? Tom crossed the finish line 3.8 seconds after Steve. Steve finished the race in 45.1 seconds. If t represents Tom's race time, which of the following equations is true?A.45.1 t = 3.8B.45.1 + t = 3.8C.t 3.8 = 45.1D.t + 3.8 = 45.1 In the open-economy macroeconomic model, if a countrys supply of loanable funds shifts right, then a. net capital outflow rises, so the exchange rate falls. b. net capital outflow rises, so the exchange rate rises. c. net capital outflow falls, so the exchange rate falls. d. net capital outflow falls, so the exchange rate rises. Which american bird does not migrate south? Find the length of RJ